RUANG LIPSCHITZ - Agustian, Muhammad Rifqi; Rosjanuardi, Rizky; Mulyaning Asih, Endang Cahya (Jurnal EurekaMatika, 2017)
ABSTRAK. Diberikan ruang metrik  dan lapangan  (real atau kompleks). Suatu fungsi dikatakan fungsi Lipschitz bernilai skalar jika terdapat konstanta  sedemikian sehingga Ruang Lipschitz  adalah ruang dari semua fungsi Lipschitz terbatas bernilai skalar pada . Didefinisikan penjumlahan dan perkalian skalar pada  dengan aturan                  dan , .Ruang Lipschitz dilengkapi dengan norm Lipschitz yang didefinisikan sebagai.Kajian ini mengkaji sifat-sifat dari fungsi Lipschitz bernilai skalar dan hubungannya  dengan ruang Banach. Kata kunci: fungsi Lipschitz, fungsi Lipschitz bernilai skalar, ruang Lipschitz, ruang Banach, norm Lipschitz. ABSTRACT. Given a metric space  and a field  (real or complex). A function is said to be scalar-valued Lipschitz function if there exists a constant  such that Lipschitz space is the space of all bounded scalar valued Lipschitz function on . Addition and scalar multiplication defined on  with                      and ,  .Lipschitz space equipped with norm Lipschitz which is defined by.This study observes the properties of scalar valued Lipschitz function and its relationship with Banach Space. Keywords: Lipschitz function, scalar valued Lipschitz function, Lipschitz space, Banach space, Lipschitz norm.